Pengaruh suhu dan lama penyimpanan terhadap parameter warna pada lettuce segar (Lactuca sativa L.) - Lenny Amelia HK (Composite : Jurnal Ilmu Pertanian, 2024)
Lettuce (Lactuca sativa L.) is a perishable vegetable that requires proper handling and storage to maintain its quality. This study aims to determine the effect of temperature and storage duration on color changes in lettuce. The research was conducted using a 4 x 3 factorial design with 2 replications in a randomized complete block design (RCBD). The treatment combinations included storage temperatures of 2°C, 10°C, and 27°C, and storage durations of 0 days, 2 days, 4 days, and 6 days. Color measurements were performed using a CR-400 chromameter with CIE technique. The results indicated that the lettuce sample stored at 2°C for 4 days (Sample l3s1) had the best color quality. The brightness parameter (L) showed good green brightness, the red-green parameter (a) indicated higher freshness, the yellow-blue parameter (b) displayed a good level of yellowness, and the total color change (∆E) showed very little color change with a value of 16.070. This condition indicates that 2°C for 4 days is the optimal storage condition for maintaining lettuce color quality.